Fatal Influenza B–MRSA Coinfection in a Healthy Adolescent: Necrotizing Pneumonia, Cytokine Storm, and Multi-Organ Failure - Irina Profir; Cristina-Mihaela Popescu; Aurel Nechita (Children, 2025)
Background: Influenza B usually causes mild illness in children. Severe and fatal cases can occur when complicated by secondary Staphylococcus aureus (S. aureus) pneumonia, including community-acquired methicillin-resistant Staphylococcus aureus (MRSA). We present a rare, rapidly progressive fatal case in an adolescent with no known medical history to highlight diagnostic and therapeutic pitfalls. Case Presentation: A 16-year-old boy with no known underlying conditions (unvaccinated for influenza) presented critically ill at “Sf. Ioan” Clinical Emergency Pediatric Hospital in Galați after one week of high fever and cough. He was in respiratory failure with septic shock, requiring immediate intubation and vasopressors. Chest X-ray (CXR) showed diffuse bilateral infiltrates (acute respiratory distress syndrome, ARDS). Initial laboratory tests revealed leukopenia, severe thrombocytopenia, disseminated intravascular coagulation (DIC), rhabdomyolysis, and acute kidney injury (AKI). Reverse transcription polymerase chain reaction (RT-PCR) confirmed influenza B, and blood cultures grew MRSA. Despite maximal intensive care, including mechanical ventilation, antibiotics (escalated for MRSA), antiviral therapy, and cytokine hemoadsorption therapy, the patient developed refractory multi-organ failure and died on hospital day 6. Autopsy revealed bilateral necrotizing pneumonia (NP) without radiographic cavitation, underscoring the diagnostic challenge. Discussion: The initial chest radiography showed diffuse bilateral pulmonary infiltrates, predominantly in the lower zones, with an ill-defined, patchy, and confluent appearance. Such appearance, in our case, was more suggestive of rapid progressive NP caused by MRSA rather than the typical pneumococcal one. This is one of the few reported cases of influenza B–MRSA coinfection with fulminant rhabdomyolysis and autopsy-confirmed necrosis. Our fulminant case illustrates the synergistic virulence of influenza and MRSA. Toxin-producing MRSA strains can cause NP and a “cytokine storm,” causing capillary leak, ARDS, shock, and DIC. Once multi-organ failure ensues, the prognosis is grim despite aggressive care. The absence of early radiographic necrosis and delayed anti-MRSA therapy (initiated after culture results) likely contributed to the poor outcome. Conclusions: Influenza B–MRSA co-infection, though rare, demands urgent empiric anti-MRSA therapy in severe influenza cases with leukopenia or shock, even without radiographic necrosis. This fatal outcome underscores the dual imperative of influenza vaccination and early, aggressive dual-pathogen targeting in high-risk presentations.